2020
DOI: 10.1111/jsap.13184
|View full text |Cite
|
Sign up to set email alerts
|

The utility of combined urine dipstick analysis and specific gravity measurement to determine feline proteinuria

Abstract: Objectives To assess the utility of urine dipstick strips for detection of feline proteinuria when used in combination with urine‐specific gravity, compared with urine protein‐to‐creatinine ratio as the gold standard. Materials and Methods Retrospective analysis of clinical records of comprehensive urine examination obtained from cats presented to a referral hospital. Diagnostic agreement and test accuracy were calculated for the dipstick test alone and in combination with the urine‐specific gravity, using dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
6
0
2
Order By: Relevance
“…In contrast to dogs, this study highlights that it is not possible to predict levels of feline proteinuria from the combination of dipstick tests and USG. This was also recently suggested by Pérez-Accino et al [ 21 ]. For the reasons stated above, we advise the systematic use of UPCR to diagnose proteinuria in cats, following the International Renal Interest Society recommendation [ 4 , 22 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast to dogs, this study highlights that it is not possible to predict levels of feline proteinuria from the combination of dipstick tests and USG. This was also recently suggested by Pérez-Accino et al [ 21 ]. For the reasons stated above, we advise the systematic use of UPCR to diagnose proteinuria in cats, following the International Renal Interest Society recommendation [ 4 , 22 ].…”
Section: Discussionsupporting
confidence: 83%
“…Although the urine was yellow, the urinary pH was 8.5. Since alkaline urine may induce false-positive results on a dipstick proteinuria test, this was considered a false-positive [ 21 , 22 ]. In contrast to dogs, this study highlights that it is not possible to predict levels of feline proteinuria from the combination of dipstick tests and USG.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find any difference in correlation between UPCR and DUR in cats, no cats had hyposthenuric samples and a difference in correlation might still exist when comparing very dilute with very concentrated samples. However, when evaluating the use of urine dipsticks for protein detection in cats, a previous study found that the grouping of urine samples based on USG did not improve the accuracy of the dipstick result to predict UPCR 20 . Another study in dogs evaluating the relationship between USG and UPCR reported that although mild to moderate negative correlations existed between these 2 variables, the use of a predictive equation could not reliably predict the UPCR based on dipstick protein results 7 .…”
Section: Discussionmentioning
confidence: 99%
“…7 Likewise, evaluating feline urine samples, another previous study reported that, for the detection of a UPCR >0.2, the application of a USG cutoff >1.035 moderately improved the accuracy of dipstick protein readings but did not improve agreement between dipstick and UPCR results. 20 T A B L E 5 Diagnostic accuracy of dipstick USG ratio (DUR) for the detection of proteinuria in cats. Abbreviations: AUC, area under the curve; CI, confidence interval; NPV, negative predictive value; PPV, positive predictive value; UPCR, urine protein creatinine ratio.…”
Section: Discussionmentioning
confidence: 99%
“…In 2 Studien lag die Sensitivität des Proteintestfeldes für Katzenurin (Cut-off 30 mg/dl) zwischen 64 % und 100 % und die Spezifität zwischen 41 % und 70 % [52,84]. Auch in Kombination mit dem USG kann bei Katzen der Grad der Proteinurie durch den Teststreifen nicht vorhergesagt werden [84,90]. Sowohl positive als auch negative Reaktionen des Proteintestfeldes sind bei Katzen höchst unzuverlässig [52,84,90].…”
Section: Leukozyten Und Nitritunclassified